Effects of Patient Education Documentation Sheet (PEDS) on Patient Education Activities and Documentation of Nurses in DLSUMC - Song-Tejada, Nida C. (2002)
BACKGROUND. Giving patient education as part of health promotion is one of the increasing concerns in surviving a competitive health care environment. Much more, the issue on the effective delivery of patient education is escalating. Among the members of the health team, nurses greatly spent time with the patient in the hospital. Nurses therefore have the prime responsibility and are in the best position to give patient education. In the event of evidence-based nursing, it is hard to identify if a nurse indeed renders patient education activities. With this, the researcher devised an administrative tool that would address such concern. The administrative tool was referred to as patient education documentation sheet or PEDS. OBJECTIVES OF THE STUDY. This study was conducted to: (1) identify if the use of PEDS will: (1.1) increase patient education activities in terms of nurse-documented activities, patient-reported activities and (1.2) improve level of patient satisfaction; (2) identify whether there was a correlation between the group that used the PEDS and the group that used the current documentation sheet in terms of nurse-documented activities and patient-reported activities; (3) to identify whether there was a significant relationship between the group that used the PEDS and the group that used the current documentation sheet in terms of nurse-documented activities and patient satisfaction; and patient-reported activities and patient satisfaction. SAMPLE. There were two groups of respondents involved in this study, patients and nurses. There were 8 nurses from the experimental group and 8 nurses from the control group. On the other hand, there were 39 patients from the experimental group and 36 from the control group. METHOD. The study applied an evaluation research using quasi experimental post-test only approach. Assignment of experimental and control groups was done by random group assignment throug a toss of a coin. All newly admitted patients at two private wards of DLSUMC, an ISO 9001 certified tertiary hospital, who met the inclusion-exclusion criteria on the experimental group had the PEDS attached to their medical record while the current documentation sheet was utilized by the control group. For the nurse documentation, nurses in the experimental group recorded the date and put their initials on the corresponding apaces on the PEDS every patient education activities rendered and nurses in the control group documented their patient education activities on the current documentation sheet. For patient report, patients were interviewed regarding the topics of patient education they received and their level of satisfaction. The latter was accomplished with the use os a patient satisfaction questionnaire. Two trained research assistants collected this data. On the last day of the intervention, nurses on the experimental group filled up the PEDS evaluation questinnaire. DATA ANALYSIS. T-test utilized to determine whether using PEDS increased nurse documentation and patient education activities. Generalized linear model and logistic regression were utilized to control the effect of age on nurse documentation and patient-reported activities. To identify if there is a correlation between nurse-documenteda activities, Pearsons Moment Product Correlation Analysis was utilized. On the other hand, Spearman's rho was used to identify the relationship between nurse-documented activities versus patient satisfaction and patient-reported activities versus patient satisfaction. Descriptive statistics was used to dentify the perception of nurses on the use of PEDS in terms of its content, usage, effects on patient education activities and documentation.
RESULTS. Results showed that the PEDS increased the nurse-documented activities of patients education (p=0.00) and patient-reported activities of nurses (p=0.00). The level of satisfaction was also improved with the use of PEDS (p=0.006. However, there was a positive correlation noted between nurse-documented activities and patient-reported activities (r=0.375; p=0.001); nurse-documented activities and patient satisfaction (rho=0.314; p=0.005); and patient-reported activities and patient satisfaction. CONCLUSIONS. It may be concluded from this study that the use of PEDS both increased the number of nurse-documented activities as well as patient-reported activities. Similarly, PEDS improved the level of patient satisfaction with the nursing sevice. The following were proven to be correlated: (1) nurse-documented activities and patient-recorded activities; (2) nurse-documented activities and patient satisfaction; and (3)patient-reported activities and patient satisfaction. RECOMMENDATIONS. Based on these findings, it is recommended that the nusing administrator of DLSUMC study and possibly integrate the Patient Education Documentation Sheet (PEDS) into their regular documentation system. For ANSAP members, to develop and formulate administrative guidelines in their own institution to improve documentation of patient education activities. Other researchers are encouraged to replicate this study on various nursing areas/facilities most especially in specialized are to validate results of this study and to enhance generalizability. A longer follow-up period for evaluation to demonstrate the sustainability of the beneficial effects of the documentation sheet may also be done. To deal with other administrative issues apart from those addressed in this study and to find out factors why nurses still fail to document despite of a convenient form.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Patient education -- Philippines